Geothermal trigeneration systems with Organic Rankine Cycles: Evaluation of different plant configurations considering part load behaviour. (May 2023) - Schifflechner, Christopher; Kuhnert, Lara; Irrgang, Ludwig; Dawo, Fabian; Kaufmann, Florian; Wieland, Christoph; Spliethoff, Hartmut
Abstract: Due to the increasing importance of cooling applications, geothermal trigeneration systems might be of high interest in the future. This work aims at evaluating different plant layouts against the background of more advanced plant configurations and part load behaviour. Five different plant configurations are analysed for geothermal heat source temperatures between 110 and 150 °C. The highest net power output is achieved by an advanced serial-parallel configuration (ASPC), but in case of high heating and cooling demand, a standard serial-parallel configuration is more favourable. For the considered base demand scenario of 130 °C, the ASPC results in an annual net power generation of 20.94 GWh, which is 6.9% higher than the second favourable configuration. The application of a recuperator within the ORC system has a significant impact on the serial concepts, but only marginally increases the power output of the parallel layouts. Comparing two exergetic efficiencies highlights that the assumed definition can result in a different ranking of the plant layouts. Considering the exergy that is transferred from the brine to the trigeneration system reveals the highest exergetic efficiency for a serial configuration, while the focus on the available exergy flow reveals the highest efficiency for the ASPC layout. Considering a brine temperature of 130 °C results in a maximal achievable second law efficiency of 34.1% if evaluating the available exergy flow. The evaluation of the pay-back period reveals that the ASPC results in the shortest pay-back period of 13.8 years. Highlights: Investigation of several plant configurations considering part-load operation. Highest net power output is achieved by an advanced serial-parallel configuration. For each plant configuration, there is an optimal desorber temperature of the AC. A pay-back period of 14 years can be achieved.